A New Multi‐Phase Field Model for the Electrochemical Corrosion of Aluminum Alloys. Issue 9 (10th July 2022) - Chen, Qingqing; Li, Zuosheng; Tang, Sai; Liu, Wensheng; Ma, Yunzhu
Abstract: A profound understanding on the corrosion kinetics and mechanisms is crucial to help improve the corrosion resistance of alloys. Corrosion of aluminum alloys is very complex due to the interplay among a bunch of electrochemical reactions, and the influences of diversified precipitates. In this work, a new multi‐phase field method is constructed to quantitatively analyze the corrosion kinetics of aluminum alloys, and a semi‐implicit algorithm is developed to solve the numerical divergence resulted by the terms of reactions in concentration equations. Then, this new method is successfully used to simulate the pitting processes in the cases of a uniform matrix, a polycrystalline matrix, and a non‐uniform matrix with secondary phase for aluminum alloys. More generally, the framework of this multi‐phase field model can potentially be used to study the corrosion of other alloy systems, and microstructure evolution of a broad range of electrochemistry processes. Abstract : A new multi‐phase field method is constructed to analyze the corrosion kinetics of aluminum alloys, and a semi‐implicit algorithm is developed to solve the numerical divergence resulted by the terms of reactions in concentration equations. The power of the new method is verified by the simulations of pitting processes of the alloys with a uniform structure, polycrystalline, or secondary phases.